You are on page 1of 6

2010

- 1 3 2 + + 2 = 0 :
- 2 3 2 + + 2 < 0 :

2 1

3 + 5 = 1
:

2
+ 2 = 2

-3

-4

250 80 . 6%
%5

:
- 1 2 1 3 2 + + 2 = 0 :
2 1 3 2 + + 2 = 0 : 3 2 + + 2 = 0 :
2 1 = 0 2 = 1 : :
3 2 + + 2 = 0 :

1
2

2 1 = 0

4 3 2 = 1 + 24 = 25 > 0 :

= 2 4 = 1

:
=1

6
6

15
6

1 25

)2(3

= 1

2
3

4
6

1+5
6

1+ 25
)2(3

+
2

= 1
2 1

; ;1

- 2 , 3 2 + + 2
:

2
3

- 3 3 2 + + 2 :
+

1
-

3 2 + + 2




2010

3 2 + + 2 < 0 1; + :
3 + 5 = 1
- 4 2 :
+ 2 = 2
= 3 2 5 1 = 6 5 = 1 0 :

35
12

2
3

; =

: ,
= 1 2 5 2 = 2 10 = 12

= 3 2 1 1 = 6 + 1 = 7
= 12
7

12

= =7
1

3 1
1 2

1 5
2 2

=
12,7

- 5 %6 :
6
100

100
100

= 250

= 265

106
100

6
100

250 1 +

= 250

%5 :
5
100

100
100

= 80

= 76

95
100

5
100

80 1

= 80


- 1 = 2 + 3 :
- 0 : 1 31
- = 3
- = 2 + 5 + 8 + + 95 :

-2




2010

3
2

- 0 : 1 31
3
- =
2
- :

243

32

= 1 + + + +

:
-1

= 2 + 3

-
U0 = 2 + 3 0 = 2 + 0 = 2
U1 = 2 + 3 1 = 2 + 3 = 5
U31 = 2 + 3 31 = 2 + 93 = 95
- Un r = 3

n IN Un = 2 + 3n

Un+1 = 2 + 3 n + 1 = 2 + 3n + 3 = Un + 3 :
Un r = 3
- S = 2 + 5 + 8 + + 95 :
S = U0 + U1 + U2 + + U31 :
S
= 16 97 = 1552

97
2

= 32

2+95
2

= 31 0 + 1

U p +U n
2

S= np+1

-2

3
2




2010

-
1

= =1
3

2
243
32

1
31
21

30
20

= 0

= 1
35
25

= 5

Un
3

2
3

= :

3
2

3 3

2 2

3 +1
2 +1

Vn
- :

243

32

= +1
3
2

S = 1 + + + +

S = V0 + V1 + V2 + + V5 :
S
1q n p +1
1q

S = Vp
6

3
2

= 2 1

1 2
1

50+1

1 2
2 3

2 2

=1

1 2
3
1
2

S = V0

665
64

= 2




2010

64729
64

729

= 2

64

36

= 2 1

26

S = 2 1


- 1 27 42
- 2 6 4
-
-
-

:
- 1 A27 C42
A27 = 7 6 = 42

=6
-

43
2

!432
!2!2

!4

! 2! 42

= C42

6 4

: = 45 :
-

90
2

!1098
!2!8

!10
! 2! 102

2
C10
=

6
4
+ 6 = 21:

30
2

=+6

!654
!24

=+6

!6
! 2! 62

= 62 + 42




2010

-
:
:
6 4
61 41 = 6 4 = 24 :
:
: ( 21 )
. 45
45 21 = 24 :

:
1

lim 2x 3 x + 7

4 lim2 x+4

x<0 x2

x3x+7
2x+1
x4
x2

lim+

lim2

lim 2x 3 x + 7 = lim 2x 3 = 2 = - 1
1

= -2
2

x
2x

= - 3
-4

= lim+
8
0

2+4
22
0
0

x3x+7

lim+

2x+1
x+4
lim2
x<0 x2

44
22

24
22

= lim + 22 = 2 + 2 = 4

x4

lim2

x2
2 +2
2

= lim2

= lim2

4
2

lim2